Veterinary anesthesia and analgesia - Greene, Stephen A.; Grimm, Kurt A.; Lamont, Leigh A.; Robertson, Sheilah A.; Tranquilli, William J. (Ames, Iowa Wiley Blackwell, 2015)
Section 1: General Topics -- Introduction: use, definitions, history, concepts, classification, and considerations for anesthesia and analgesia -- Anesthetic risk and informed consent -- Anesthesia equipment -- Monitoring anesthetized patients -- Anesthetic emergencies and resuscitation -- Euthanasia and humane killing -- Section 2: Pharmacology -- General pharmacology of anesthetic and analgesic drugs -- Anticholinergics -- Adrenergic agents -- Sedatives and Tranquilizers -- Opioids -- Non-steroidal anti-inflammatory drugs -- Anesthetic and analgesic adjunctive drugs -- Muscle relaxants and neuromuscular blockade -- Injectable anesthetics -- Inhalation anesthetics -- Local anesthetics -- Section 3: Body fluids and thermoregulation -- Acid-base physiology -- Perioperative thermoregulation and heat balance -- Treatment of coagulation and platelet disorders -- Clinical pharmacology and administration of fluid, electrolyte, and blood component solutions -- Section 4: Cardiovascular system -- Cardiovascular physiology -- Cardiac output measurement -- Anesthesia for cardiopulmonary bypass -- Cardiac pacemakers and anesthesia -- Pathophysiology and anesthetic management of patients with cardiovascular disease -- Section 5: Respiratory system -- Physiology, pathophysiology, and anesthetic management of patients with respiratory disease -- Section 6: Nervous system -- Physiology, pathophysiology, and anesthetic management of patients with neurologic disease -- Nociception and pain -- Section 7: Hepatic system -- Physiology, pathophysiology, and anesthetic management of patients with hepatic disease -- Section 8: Gastrointestinal and endocrine systems -- Physiology, pathophysiology, and anesthetic management of patients with gastrointestinal and endocrine disease -- Section 9: Urogenital system -- Physiology, pathophysiology, and anesthetic management of patients with renal disease -- Anesthetic considerations for renal replacement therapy -- Anesthetic considerations during pregnancy and for the newborn -- Section 10: Comparative anesthesia and analgesia -- Comparative anesthesia and analgesia of dogs and cats -- Anesthesia and pain management of shelter populations -- Comparative anesthesia and analgesia of equine patients -- Comparative anesthesia and analgesia of ruminants and swine -- Comparative anesthesia and analgesia of laboratory animals -- Comparative anesthesia and analgesia of zoo animals and wildlife -- Comparative anesthesia and analgesia of aquatic mammals -- Comparative anesthesia and analgesia of reptiles, amphibians, and fishes -- Comparative anesthesia and analgesia of birds -- Section 11: Anesthesia and analgesia for domestic species -- Dogs and cats -- Canine and feline local anesthetic and analgesic techniques -- Horses -- Horses with colic -- Equine local anesthetic and analgesic techniques -- Ruminants -- Swine -- Ruminant and swine local anesthetic and analgesic techniques -- Section 12: Anesthesia and analgesia for selected patients or procedures -- Ophthalmic patients -- Neonatal and pediatric patients -- Senior and geriatric patients -- Cancer patients -- Orthopedic patients -- Patient and anesthetist safety considerations for laser and radiographic procedures and magnetic resonance imaging.
Includes bibliographical references and index.
Keywords: Veterinary anesthesia; Anesthesia -- veterinary; Analgesia -- veterinary